2002
DOI: 10.1097/00007890-200204270-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning: a defense mechanism against the reactive oxygen species generated after hepatic ischemia reperfusion1

Abstract: Preconditioning, by blocking the xanthine/XOD pathway for ROS generation, would confer protection against the liver and lung injuries induced by hepatic I/R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 43 publications
3
84
1
4
Order By: Relevance
“…The results are in agreement with the reports of Cavalieri et al [5] . Peralta et al [6] , showed that IPC could block the xanthine oxidase pathway of ROS generation, thus providing protection against liver I/R injury. Diminishing ROS production contributes to the mechanism of IPC injury-preventive effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are in agreement with the reports of Cavalieri et al [5] . Peralta et al [6] , showed that IPC could block the xanthine oxidase pathway of ROS generation, thus providing protection against liver I/R injury. Diminishing ROS production contributes to the mechanism of IPC injury-preventive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of antioxidants such as glutathione, quercetin, could afford protection against ischemia/ reperfusion injury [3,4] . It has been shown that ischemic preconditioning can prevent the formation of ROS after I/ R, thus exerting protection to the liver [5,6] . To control the detrimental effects of ROS, organisms have developed a variety of antioxidant defense systems, especially the endogenous antioxidant enzymes system including superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx).…”
Section: Introductionmentioning
confidence: 99%
“…Because administration of antibodies against Pselectin or TNF-␣ prior to ischemia was seen to have the same effect as preconditioning, it has been suggested that the blockade of P-selectin upregulation probably results from inhibition of systemic TNF release from Kupffer cells [88]. Moreover, recently it was reported that ischemic preconditioning was able to increase the hepatic tolerance against reperfusion injury by attenuating the release of ET [89] and the production of ROS, either by blocking the xanthine-oxidase pathway or by preserving the mitochondria structure [90,91]. In this last work it was also reported that well-preserved mitochondria were associated with an attenuated release of cytochrome c to the cytoplasm, as well as with a low index of caspase-3 activity [91].…”
Section: Protective Mechanisms Of Delayed Ischemic Preconditioningmentioning
confidence: 97%
“…The underlying mechanism is thought to rely on the modification of gene expression resulting in protein production as its effectors [110] . Various substances have been implicated as key effectors in liver IPC including adenosine [111][112][113][114] , protein kinase C [115][116][117] , NO [118][119][120][121] , heatshock proteins [122,123] , tyrosine kinases [124] , MAPKs [117] , oxidative stress [125,126] and NF-κB [127,128] . The beneficial effects of IPC on the liver following IRI include decrease in severity of liver necrosis [129] , antiapoptotic effects [130] , preservation of liver microcirculation [131,132] and improvement in survival rate [119] , and more recently, its role in liver regeneration is currently being evaluated.…”
Section: Ischaemic Preconditioning In Liver Regenerationmentioning
confidence: 99%